Assessing the Role of Electronic Payment Systems in Financial Institutions. A Case of a Savings Bank in Zimbabwe (Global Journal of Management and Business Research, 2014)
This research sought to evaluate the role of electronic payment systems in financial institutions using a case of a Savings Bank in Zimbabwe. The research objectives were; to find the types of electronic payment systems used by the savings bank, to assess the role of electronic payment systems on operations of the savings bank and to find the merits and demerits of using electronic payment systems in savins banking. This research used a descriptive survey design. The findings were based on data obtained from 20 savings bank employees, 40 savings bank customers and five savings bank top managers from Causeway and Bindura branches. Questionnaires and face to face interviews were used to obtain primary data and secondary data was obtained through studying information from internet online publications, textbooks as well as latest newspaper articles.
Keywords: electronic payment system; ecocash; western union; telegraphic transfers